PERAN AGAMA ISLAM TERHADAP PENGARUH KESEHATAN MENTAL PADA MAHASISWA UIN JAKARTA - Ida Septiani Sari; Nasichah, Tiara Syaumi Rizki, Muhamad Zaki Mubarok (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research journal investigates how mental health impacts the lives of students, especially those living in unsupportive environments. With a qualitative approach and using a Google Forms survey, this research highlights students' understanding of the definition of mental health according to the Islamic religion. So this journal has several objectives, namely to find out the influence of mental health on students' lives, the causes of students suffering from mental disorders, the relationship between Islam and mental health and the role of Islam in influencing students' mental health. The results show that the majority of respondents consider the role of Islam in influencing their mental health to be important. In dealing with anxiety, most students tend to talk to other people, and listening to the recitation of the holy verses of the Koran is considered a source of calm. The Islamic perspective highlights that good mental health involves physical and mental health, as well as religious beliefs that can provide peace of mind. This study confirms that understanding and practicing the Islamic religion can be an important factor in overcoming students' mental disorders, providing in-depth insight into the role of religion in creating positive mental balance.